Permit to temporarily leave prison (Archives of Criminology, 1998)
The article is composed of four basic parts. The first one is historical: it discusses the evolution of legal regulation of various forms of permits to temporarily leave prison (except interruption of execution of the penalty of imprisonment) and the practice of granting such permits in the period preceding the adoption of the new punishment execution code [PEC]. Concerned here were: permit granted by way of reward to leave prison for up to 5 days (Art. 55 § 3 PEC); so-called compassionate permit to stay away from prison for up to 5 days (Art. 59 PEC); so called reward permit for 24 hours (§ 62.1 of Instruction on the execution of the penalty of imprisonment before its amendment of 1995); and regulation permit also granted for 24 hours (abolished by the abvementioned amendment of the Instruction). Hence the discussion contained in the first part of the paper proceeds on two different planes. On the one hand, we discuss the legal shape of the permits undergoing legislative changes and at the same time submitted them to critical dogmatic analysis. On the other hand, we strive to demonstrate the functioning of those legal solutions in penitentiary practice basing on the findings of few earlier empirical surveys and on statistical materials gathered by the prison administration since 1985.Our main focus is the practice of the 1990s when systemic transformation and the related humanization of the process of imprisonment led to considerable growth in the number of granted permits to temporarily leave prison, and the relevant legal transformations the effected, that is amendment of PEC and the Instruction on the execution of the penalty of imprisonment.The issue of permits was then broadly covered by the media which - not always competently and objectively - criticized the authorities for too many such permits granted; this led to an animated discussion in the doctrine. Critics considered this policy of penitentiary authorities too liberal; they argued it led to a growth in crime caused by prisoners released on permit thus reducing citizens’ feeling of safety, and also made it possible for prisoners to escape or to stay away from prison longer than permitted.It has not been possible to appraise the discussed policy basing on statistical data only due first of all to the fact that the material we based on contained merely data on the number of permits granted and said nothing about the grantees and their characteristics. From statistical analysis it followed merely that from 1985 till 1993, the number of permits granted went up nine times only to become reduced by 40% during the next two years. Also on a regular decrease (from 6.3 to 2.4 percent) in that period were cases of so-called ,,failure to return” - a category which, for obscure reasons, in the statistics includes both the actual failures to return to the institution and cases of late-coming; the proportions were calculated from the total of permits granted. The number of offenses committed by prisoners while on permit was rather small and ranged from 200 to 600 a year.Part two of the article discusses international penitentiary standards relating to inmates’ contacts with the outer world and contained in the UN Standard Minimum Rules of Treatment of Prisoners of 1955 and European Prison Rules of 1987. Also discussed have been provisions regulating the permits to temporarily leave prison in selected European countries: Germany, France, Belgium, Sweden, Finland, Norway, Denmark, Spain, Holland, Austria, Portugal, Italy, Bulgaria and Hungary. It could be stated basing on the analysis that the Polish regulations of the discussed sphere (even those valid before the adoption of the new punishment execution code) were consistent with international standards and by no means inferior to foreign provisions.The next part of the study discusses the findings of the authors' own research conducted on 15-31 August 1995 (that is, before the above-mentioned of PEC and rules of imprisonment) in 12 prisons and remand prisons. The tool was a questionnaire developed by the Law Enforcement Institute. Examined were the files of all prisoners who in the period from 1 January 1994 till 30 June 1995 applied for a permit to temporarily leave prison, or in whose case the application was field by prison administration, whether the permit was actually granted or refused. The sample was composed of 1,043 persons, and the number of applications was 7,336. The total of 6,524 permits were granted to 970 persons.It was found that a vast majority of permits applied for were actually granted which is to some extent accounted for by the fact that most applications were field by prison administration who subsequently supported them. Permits were granted to 93% of the sample which made as many as 6.7 permits per person on the average. What is more significant though, was that over one-fifth or the sample (22.6%) were granted 10 or more permits within a relatively short period of time which manifests the existence of a privileged group among prisoners. That same conclusion can also be drawn from the fact that, the mean length of time spent away from prison being 43 hours, 11% of the sample were on permit for 1 to 2 months, and 1.5% - for over 2 months. As regards return from permit, the proportion of prisoners who never returned was 8.4%, and over one-fourth of them were on the police wanted list during the survey. This phenomenon is the more dangerous as nearly a half of the sample (49.5% a failed to return in due time on at least one occasion. Instead, the number of offenses committed by the sample while on permit seems relatively small, the proportion of offenders being 4.3%. Offenses committed most often were burglary and robbery. Considering, however, the extremely small detectability rate in Poland, the proportion may well depart greatly from the reality.Even the above findings justify the statement as to a dubious value of appraisals of the correctness of permit granting policy basing on statistical material only. They also confirm the need for inclusion is those materials of data on the number not only of permits granted but also of grantees. Leaving aside a number of formal transgressions found in the course of research, the findings generally justify a conclusion that many permits were granted automatically, so to say. It was difficult as a rule to identify any objective criteria for granting or refusing permits; this means that the permit policy violated the principle of individualized treatment of prisoners.The article ends with general conclusions from the practice followed so far and with postulates de lege ferenda formulated on the grounds of amendments introduced by the new PEC of 6 June 1997. Not going into details of those amendments, it has to be stated that they trend towards extension of the legal possibilities of granting permits and of the length of leave thus granted.In the authors’ opinion, most of the amendments deserve to be praised which is of course not to say that none of them raise any reservations. It has to be stressed, though, that the appraisals are not too categorical as the new provisions (which enter into force on 1 September 1998) leave a considerable freedom of interpretation. The practice of their application should therefore be monitored closely to begin with; the findings will then help to verify pertinence of statutory regulations of the granting of permits to temporarily leave prison.